FAKTOR RISIKO STUNTING PADA BALITA (24—59 BULAN) DI SUMATERA - Zilda Oktarina; Trini Sudiarti (Food and Nutrition Society of Indonesia, 2013)
This study was aimed to analyze risk factors of stunting in underfive children aged 24—59 months in Sumatera. A cross sectional study was conducted in 1 239 children at Aceh, North Sumatera, South Sumatera, and Lampung Provinces who have complete variable data of the National Basic Health Research 2010. The data were collected by questionnaires and anthropometric assessment. Chi square analysis and logistic regression were used to assess the association between risk factors and stunting in children. The result showed that prevalence of stunting among children were 44.1%. The significant risk factors of stunting among subjects (p<0.05) were mother’s height (OR=1.36), fat intake (OR=1.30), family size (OR=1.38), and drinking water resources (OR=1.36). The dominant factor that associated with stunting in children was family size (OR=1.38). Researcher suggest that family can control total children with family planning program.